2007
DOI: 10.1038/mt.sj.6300131
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus Hemagglutinin Display on Baculovirus Envelope: Cytoplasmic Domain Affects Virus Properties and Vaccine Potential

Abstract: Hemagglutinin (HA) is the major immunogen on the envelope of avian influenza virus (AIV). Therefore we constructed two recombinant baculoviruses: Bac-HA, expressing histidine-tagged HA with the cytoplasmic domain (CTD) derived from HA, and Bac-HA64, expressing histidine-tagged HA with the CTD derived from baculovirus envelope protein gp64. After infection, HA with either CTD was expressed and anchored on the plasma membrane of Sf-9 cells, as revealed by confocal microscopy. Immunogold electron microscopy demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 48 publications
2
86
0
Order By: Relevance
“…Although these characteristics might be disadvantageous for the transgene expression, the baculovirus may have potency for use as a vaccine vector possessing adjuvant activity. Recombinant baculoviruses bearing the chimeric GP64 with Plasmodium berghei circumsporozoites (58,59), Plasmodium falciparum circumsporozoites (60), Toxoplasma gondii (61), rinderpest virus (62), footand-mouth disease virus (63), pseudorabies virus (64), and avian influenza virus (65) have been shown to elicit an efficient antibody response. These results suggest that recombinant and pseudotyped baculoviruses encoding or transiently bearing foreign epitopes may induce immune responses in the antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although these characteristics might be disadvantageous for the transgene expression, the baculovirus may have potency for use as a vaccine vector possessing adjuvant activity. Recombinant baculoviruses bearing the chimeric GP64 with Plasmodium berghei circumsporozoites (58,59), Plasmodium falciparum circumsporozoites (60), Toxoplasma gondii (61), rinderpest virus (62), footand-mouth disease virus (63), pseudorabies virus (64), and avian influenza virus (65) have been shown to elicit an efficient antibody response. These results suggest that recombinant and pseudotyped baculoviruses encoding or transiently bearing foreign epitopes may induce immune responses in the antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have reported the development of various antigenexpressing baculoviruses that target specific infections. [11][12][13][14][15] The recombinant baculovirus vectors strongly induced host innate and acquired immunity. We have previously reported that wild-type baculovirus induces antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] In several reports, baculoviruses were developed as vaccines against pathogens. [11][12][13][14][15] Abe et al reported that baculovirus-infected host cells produced type I interferons and proinflammatory cytokines through Toll-like receptor 9 and interferon regulatory factor 7 signaling. 16,17 Schütz et al reported that baculovirus-infected, human monocyte-derived DCs expressed cell-surface activation markers and produced tumornecrosis factor alpha (TNF-a).…”
Section: Introductionmentioning
confidence: 99%
“…22 Another appealing application of baculovirus is in vivo gene delivery, but most previous in vivo studies delivered only reporter genes into animal models. 23 28 show that a baculovirus expressing diphtheria toxin A inhibits the glioma xenograft growth in the rat brain, suggesting the potentials of baculovirus in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%